SOCIAL AND MEDICAL RISK FACTORS OF COVID-19 DISEASE - Omonov Olimjon; Erkinova Nigora; Babajanova Zamira (The Bioscan, 2025)
This study was conducted based on a retrospective study of the medical histories of patients who were hospitalized with a diagnosis of COVID-19 in the Bukhara Regional Multidisciplinary Hospital and the Bukhara Regional Infectious Diseases Hospital in 2020-2022. Like all infectious diseases, COVID-19 has its own social characteristics. That is, in this case, the age of patients, their region of residence, social strata of the population, and gender characteristics can have a different impact on the spread of the disease. The social characteristics of the population directly cause changes in the occurrence of medical risk factors in one way or another during the spread of the disease. In turn, the development of medical risk factors also sharply reduces the effectiveness of treatment for the disease. Therefore, the social and medical factors mentioned above are being studied extensively worldwide. This article discusses the likelihood of developing medical risk factors, analyzing each of the social factors listed above separately.